PRARANCANGAN PABRIK ASETANILIDA DARI ANILIN DAN ASAM ASETAT KAPASITAS 20.000 TON PER TAHUN - Choiron, Alfian Achmad; MUJIBURROHMAN, MUHAMMAD S.T.,M.T.,Ph.D; Erawati, Emi S.T.,M.Eng (2016)
Acetanilide (± 95%) is a product that is widely used as raw materials in the pharmaceutical industry, which is the raw material for analgesic and antipiretic. Factory acetanilide of aniline and acetic acid was established due to the need for the increase from year to year. Acetanilide factory is designed to meet the domestic demand and the possibility to be exported. Acetanilide mill is designed with a capacity of 20,000 tons per year in operation for 330 days per year. Acetanilide making process is done by liquid phase acylation reaction amide mole ratio of aniline: acetic acid = 1: 2. The reaction is exothermic and is run in a reactor countinous Stirred Tank Reactor, liquid-liquid phase, reversible and kept isothermal operating conditions (120oC) and a pressure of 1 atm. Acetic acid requirement for this plant as much as 1282.87 kg / h and needs aniline as much as 1839.23 kg / hour. Products such as acetanilide 2550.315 kg / hour. Support utilities includes water supply process of 28326.44 kg / h obtained from Bengawan Solo river water, the supply of saturated steam at 1225.991 kg / h obtained from the boiler with fuel oil amounted to 210.830 liters of fuel per hour, the need for compressed air 56.0736 m3 / h, the demand for electricity is obtained from the PLN and two sets of 269.6849 kW generator as a backup, as much fuel as 344.13 kg / hour. The factory was established in an industrial location Karanganyar, Central Java province with a land area of 11,500 m2 and the number of employees 150 people. Acetanilide mill uses fixed capital of Rp 328,351,548,785.16 and working capital of Rp 79,199,566,980.81. From the economic analysis of this plant demonstrates a profit before tax of Rp 149,489,405,829.24 per year after taxes 20% profit reached Rp 119.591.524.663.39 per year. Percent Return On Investment (ROI) before tax and after tax 45.5% 36% Pay Out Time (POT) before taxes for 1.80 years and 2.15 years after tax. Break Even Point (BEP) amounted to 43.45%, and Shut Down Point (SDP) of 19.519%. Discounted Cash Flow (DCF) accounted for 46 %%. From the data above feasibility analysis concluded that the plant is profitable and feasible to set. Keywords: acetanilide, acetic acid, aniline